2021
DOI: 10.1038/s41598-021-81490-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gasoline additive on combustion and emission characteristics of an n-butanol Partially Premixed Compression Ignition engine under different parameters

Abstract: The experiments were conducted on a modified two-cylinder diesel engine to investigate the effects of excess-air coefficient (λ) and intake temperature (Tin) of different blending ratios (volume ratio of gasoline in the blends) on the combustion and emission characteristics of a Partially Premixed Compression Ignition (PPCI) engine. The results show that with the increase of gasoline blending ratio, the peak in-cylinder pressure (Pmax), the peak in-cylinder temperature (Tmax) and the peak heat release rate (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Also, lower specific fuel consumption is another attractive benefit of the HCCI engine. Through, visualizing the combustion process of conventional SI engines and HCCI engines, it was found that flame propagation was easily seen in SI engine combustion whereas not able to see in HCCI engines (2) . Thus, proving that better volumetric combustion has occurred during HCCI combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, lower specific fuel consumption is another attractive benefit of the HCCI engine. Through, visualizing the combustion process of conventional SI engines and HCCI engines, it was found that flame propagation was easily seen in SI engine combustion whereas not able to see in HCCI engines (2) . Thus, proving that better volumetric combustion has occurred during HCCI combustion.…”
Section: Introductionmentioning
confidence: 99%
“…These two pollutants could be reduced by lowering the combustion temperature and raising the premixed combustion ratio as much as possible 1 . As a consequence, innovative combustion modes such as homogeneous charge compression ignition (HCCI) 2 , premixed charge compression ignition (PCCI) 3 , 4 , partially premixed combustion (PPC) 5 , and RCCI 6 have been proposed. The RCCI combustion mode is characterized by the presence of two distinct fuel supply systems.…”
Section: Introductionmentioning
confidence: 99%